Children’s literature with black protagonism: an analysis of teaching sequences for an anti-racist education (Research, Society and Development, 2022)
The present article is a clipping from the dissertation called “Ethnical-racial relationships in children’s education: literature as a pedagogical tool for the enforcement of Law no. 10.639/03 regarding the construction of an anti-racist education” which aimed at identifying the contribution of the usage of children’s literature with black protagonists as a powerful instrument for the enforcement of Law no. 10.639/03. It methodologically used the collaborative research-action by Ibiapina (2008), having, as subjects involved, a Children’s Education teacher, the researcher (as agent-collaborator in the classroom – story reader) and 17 pre-school students from a municipal school in Canguçu/RS. For data collection the following was used: records in photos, audios, videos and a field diary. For corpus treatment and analysis, we observed the studies of Content Analysis (AC) by Bardin (2016). This clipping presents the analysis of the educational interventions anchored in the works “Amoras” (EMICIDA, 2018) and “O Pequeno Príncipe Preto para Pequenos” (FRANÇA, 2020). The results highlighted that the work with literature with black protagonism may be a challenge for teachers due to the rooting of structural racism in the school environment. However, this educational pratice proved to be promising to make the Law no. 10.639/03 effective.